Comparison Of Silane Treatment Methods On Filler Reinforcement In Rubber Composties - Anuar, Azila (Universiti Sains Malaysia, 2017)
The objective of this study was to compare the performance of different silane treatment methods to assess the optimum methods for improvement of interfacial bonding between fillers and matrix. The methods used were dry method, aqueous method and melt blending method. In order to check the effectiveness of the applied methods for surface modification of fillers, three different types of fillers: silica (nano size), ferrite (macro size), and kenaf (fibers) were investigated. Evidence that silane linkages between fillers and rubber matrix had occurred was identified by Fourier transform infrared spectroscopy (FTIR). Crosslink density assessment by swelling test provided evidence that the tetrasulphane group of bis-(3-triethoxysilylpropyl) tetrasulphane (TESPT) formed crosslink with the rubber molecular chains. Morphology of the fracture surface of the rubber with untreated and treated filler was examined using scanning electron microscope (SEM). Tensile strength, elongation at break and M100 were measured using the universal tensile tester. The results exhibited the advantages of TESPT as a coupling agent between fillers and rubber matrix and also revealed that the dry method produced the optimum interfacial bonding when compared with aqueous method and melt blending metho